Field Marshal Sam Manekshaw, M.C. : soldiering with dignity - Singh, Depinder (Dehradun : Natraj Publishers, 2002)
On the life and military career of an Indian marshal and his contribution towards history of Indian army.
Includes index.
Keywords: Manekshaw, Sam, -- 1914-2008.; Manekshaw, Sam, -- 1914-2008 -- Career in the military; Generals -- India -- Biography; Armed Forces -- Officers -- Biography